Analisis Pemanfaatan Teknologi Digital dalam Transformasi Proses Pembelajaran - Salsabila, Nazwa; Manalu, Gresia Br; Saleh, Muhammad; Chery, Muhammad Rifaldi; Damar, Rafif Abdullah; Marpaung, Veymas Februardandi; Pulungan, Hendra Kurnia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the transformation of learning through the utilization of digital technologies in Indonesian educational institutions. By adopting the literature study method, this study analyzes various scholarly sources to understand the dynamics of technology implementation in the pedagogical process. Findings show that digital technologies make a significant contribution in creating more interactive learning, expanding accessibility of information, as well as improving the quality of education. Nevertheless, various constraints are still faced, including infrastructural limitations, educators’ competence in utilizing technology, as well as budget constraints. To optimize the implementation of technology in learning, a comprehensive strategy is needed that includes the provision of adequate infrastructure, the capacity building of educators, as well as the formulation of policies that support the integration of technology in the education system.